2018
DOI: 10.3233/rnn-180822
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic and kinetic benefits of implantable peroneal nerve stimulation in people with post-stroke drop foot using an ankle-foot orthosis

Abstract: This study substantiates the evidence that implantable peroneal FES as a treatment for post-stroke drop foot may be superior over AFO in terms of knee stability, ankle plantarflexion power, and propulsion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 24 publications
2
19
0
1
Order By: Relevance
“…Previous studies have also outlined the benefits of surface electrical stimulation on gait and quality of life in patients with drop foot [20, 21]. Electrical stimulation has been shown to be superior to ankle foot orthoses regarding knee stability, ankle dorsal extension power, propulsion [22] the ability to negotiate a sudden obstacle [23] and based on patients’ preferences [19, 24]. However, literature is inconclusive on whether functional electrical stimulation should always be preferred over ankle foot orthoses [15] and both seem to be equally effective regarding increases in walking speed and activity level [19, 24].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also outlined the benefits of surface electrical stimulation on gait and quality of life in patients with drop foot [20, 21]. Electrical stimulation has been shown to be superior to ankle foot orthoses regarding knee stability, ankle dorsal extension power, propulsion [22] the ability to negotiate a sudden obstacle [23] and based on patients’ preferences [19, 24]. However, literature is inconclusive on whether functional electrical stimulation should always be preferred over ankle foot orthoses [15] and both seem to be equally effective regarding increases in walking speed and activity level [19, 24].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown good intra-and interexaminer reliability of the gastrocnemius medialis (GM) muscle PA evaluated with USI in poststroke patients, and the PA measured by USI was clinically useful assessment of rehabilitation effects in poststroke patients (Cho, Cho, Yoo, Lee, & Lee, 2018;Cho, Lee, & Lee, 2014). Spastic hemiplegia patients usually present with foot-drop and their ankle dorsiflexion was impaired, which is associated with the increased muscle tone of the calf muscles (Berenpas et al, 2018;Singer, Dunne, & Allison, 2001;Soltani, Rahimi, Naimi, Khademi, & Saeedi, 2014). Spastic foot-drop would also increase plantar load distribution of the forefoot on the affected side (Berenpas et al, 2018;Soltani et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Spastic hemiplegia patients usually present with foot‐drop and their ankle dorsiflexion was impaired, which is associated with the increased muscle tone of the calf muscles (Berenpas et al, ; Singer, Dunne, & Allison, ; Soltani, Rahimi, Naimi, Khademi, & Saeedi, ). Spastic foot‐drop would also increase plantar load distribution of the forefoot on the affected side (Berenpas et al, ; Soltani et al, ). The lateral gastrocnemius, GM, and the soleus consist of the triceps surae muscle group, and determine the plantar flexors of the ankle.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not well-tolerated in all patients [10]. In recent years, gait improvement has been achieved using functional electrical stimulation (FES) [1, 10, 16, 23, 25], which combines the orthotic benefits of an AFO with a more physiological approach that involves muscle contraction and the related sensory feedback [10, 25]. Transcutaneous FES (tcFES) of the peroneal nerve has been associated with significantly reduced falls compared to intensive physiotherapy [7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a systematic review of FES in MS patients indicates increased gait speed using FES [19]. Semi-implantable FES (siFES) of the peroneal nerve has been found to increase gait speed and improve gait patterns compared with a baseline without stimulation [6, 10, 17], compared to orthotic devices [1, 23], and also compared to tcFES [17]. The findings of a systematic review, including predominantly chronic stroke patients, however, did not suggest a difference between tcFES and siFES in terms of walking speed [13].…”
Section: Introductionmentioning
confidence: 99%